The Effect of Vowels in Children’s Speech Therapy Disorders (Journal of the College of Basic Education, 2022)
Phonologists attempted to divide language speech sounds into two main categories, i.e. vowels and consonants. Vowels' functions are characterized by their physical and articulated features, which made these sounds more audible and extended. Thus, vowels are the first sound produced by children in their early stages of articulation, before any exposure to linguistic samples to be imitated. Accordingly, the researcher tries to study the potentiality of using such distinguished vowel properties in the treatment of speech therapy disorders, which was the focus of psychologists for decades who studied the methods of such treatment and the ways of their diagnosis. On the basis of the results obtained, psycholinguistic studies help treat such speech therapy disorders.